A leitura significativa do texto escrito: recursos léxico-gramaticais no espaço do ensino-aprendizagem da educação formal - Leite, Rosemeire Moreira (2015)
This dissertation was written by following reading, writing and teaching research of Portuguese language, belonging to the postgraduate Studies program in Portuguese Language from the Pontifical Catholic University of São Paulo and discusses the processes of construction of senses, developed through the reading of written text. Based on the principles and assumptions of Linguistic Education, as well as the Textual Linguistics of interacting strand partner, this research has as main objective the reflection on theories and practices for training proficient readers, capable of assigning senses to written texts, by means of dialogue and interaction with them. Although the reading is themed in many academic research of significant prestige, there is still much to be achieved in the teaching-learning practices of this theme in formal school. Thus, the motivation of this work associates to lousy results revealed by national and international assessments focused on characterization of regular school formed by contemporary readers. To this end, studies will be organized, initially by a literature search of historiographical character, in order to situate historically formal education with regard to the teaching of reading text written in their origins and, subsequently, by the presentation of methods and conceptions of reading and its meaningful learning, culminating in a proposal of didactic sequence guided by principles of Linguistic Education that guide this dissertation